Digital hoarding behaviours: Underlying motivations and potential negative consequences. (August 2018) - Sweeten, George; Sillence, Elizabeth; Neave, Nick
Abstract: Hoarding behaviours associated with the accumulation of physical objects has become a newly diagnosed psychiatric disorder, with the demographic, social and psychological characteristics of individuals who hoard items being reasonably well established. Online forums, blogs, and the media have long-speculated about the existence of 'digital hoarding' (the over-accumulation of digital materials such as emails, photographs, files and software), and the extent to which it may be a 'problem'. However, identifying the characteristics of and potential problems associated with digital hoarding has thus far received little scientific attention. The current qualitative study gathered data from 24 females and 21 males aged 20–52 and asked them about their digital hoarding behaviours, underlying motivations and potential negative consequences. The questions covered both personal and work-place materials. Thematic analysis identified themes common to physical hoarding, these related to the over-accumulation of digital materials, difficulties in deleting such materials, and feelings of anxiety relating to this accumulation/difficulty deleting. Some differences were found in relation to work versus home. The implications of the findings and suggestions for future research are discussed. Highlights: Confirmed the existence of 'digital hoarding' via qualitative data gathered online. Digital hoarding relates to excessive accumulation, deletion difficulty and anxiety. Motivations differed between workplace and personal digital information settings.